Student Reports in the Digital Age: An Invitation to Classroom Inquiry on Controlled Research - Willow I. Brown; Howard A. Klein; Judith Lapadat (Networks: An Online Journal for Teacher Research, 2009)
The digital age provides an overwhelming amount of information and an array of modes, including text, images, and sound, for presenting student learning. Without a comprehensive strategy for teaching information processing and presentation, student reports can be overwhelming for both students and teachers. The authors present research platforms as explicit instruction with potential to scaffold students toward multimodal literacy and purposeful independent inquiry presented with a confident voice. In research platforms, teachers create multimodal text sets on topics of interest and guide students to collect information, make sense of it, and present it to peers in engaging formats. Rather than advocate the research platform strategy as tested and true, the authors invite readers to join an electronic network, a virtual community of practice, to share text sets and reflect collaboratively on student responses. The authors expect to report developmentand evaluation of the strategy and of the network in subsequent articles.